A mixed-methods evaluation of a longitudinal primary–secondary school transitions support intervention - Bagnall, Charlotte Louise; Stevenson, Elizabeth; Cookson, Darel; Jones, Frederick; Garnett, Nicholas James (Frontiers in Psychology, 2024)
Primary-secondary school transitions are critical transitions for children, which can be emotionally demanding longitudinal experiences, that can positively and negatively impact future emotional wellbeing and mental health. However, interventions that have been developed to reduce the negative outcomes children commonly experience are limited in number, sustainability, and reach, and rely on cross-sectional, as opposed to longitudinal evaluations. The current study evaluates, Transition 5-7, a universal, class-based nine-week intervention to develop children's awareness and ability to cope with the multiple changes experienced over primary-secondary school transition.The evaluation utilised a mixed-methods approach, combining both quantitative outcome and qualitative process intervention evaluation. For the outcome evaluation, a quasi-experimental research design was used, and intervention and comparison group children completed a questionnaire in Year 5 (n= 185), Year 6 (n=217) and Year 7 (n=162), which assessed their self-reported perceptions of Transition Worries, Transition Excitement, Emotional Wellbeing, Parental Support, and Coping Efficacy. To understand the implementation of Transition 5-7, three focus groups were conducted with Year 6 children, 3 interviews with teachers, and one interview with the Transition Manager of the local government education authority at the time of the project, who developed Transition 5-7.The outcome evaluation found that children participating in the intervention showed a decrease in Transition Worries and an increase in Transition Excitement and Coping Efficacy compared to the comparison group, resulting in a lowered impact on Emotional Wellbeing, over time. The need for a more systemic approach to primary-secondary school support provision, which is gradual, has a distinct delivery, and follows a skills-based curriculum, was discussed in the process evaluation.Meta-inferences drawn demonstrate the importance of gradual emotional centred transition provision embedded within Year 5, 6 and 7.